Formation mechanism of adhering powder and improvement of the surface quality during laser solid forming. Issue 5 (September 2016) - Tan, Hua; Hu, Guang; Zhang, Fengying; Fan, Wei; Hou, Wei; Huang, Weidong
Abstract Laser solid forming (LSF) is a promising manufacturing technology. During the LSF process, the adhering powder has a significant impact on the surface quality of the laser solid forming part. In this study, the formation mechanism of the adhesion particle was discussed. It was shown that only the powder particles fed into the rear edge of the molten pool might form the surface adhering powder. Then, an interaction model of powder particles and molten pool edge was established based on the theory of elasticity and force analysis. The critical condition of spherical particle adhesion and rebound at the molten pool edge was obtained, which indicated that the particle speed and particle size had an important influence on the formation of the surface adhering powder. The smaller the powder particle is, the higher the critical speed of particle rebound at the molten pool rear edge is. Further, the verification experiments were conducted and the results agreed with the analysis. Finally, the forming process improvement was made based on the formation mechanism of the adhering particle, and the components with improved surface quality were obtained.